The Rationality and Price Effects of u.s. Department of Agriculture Forecasts of Oranges. - Baur, Robert F; Orazem, Peter F (Journal of Finance, 1994)
This article examines the effect of public information on the orange juice market. The authors investigate the rationality, information content, and price effects of U.S. Department of Agriculture forecasts of the production of oranges. U.S. Department of Agriculture forecasts are found to be unbiased and efficient. The first forecast contains the most new information and subsequent reports become valuable only when freezes occur. Significant price movements occur in response to announced production in both Florida and California. However, the majority of price variations cannot be explained by these movements in supply.